MODEL INTEGRATIF GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWANGENERASI Z DI INDONESIA: PERAN MEMEDIASI WORKPLACE WELLBEING - Dhyah Harjanti; Noerchoidah Noerchoidah; Francis Daniel Juventino; Amanda Rizky Rossitika (CAPITAL: Jurnal Ekonomi dan Manajemen, 2025)
Loyalty from employees is vital for the long-term success of a business, especially when it comes to Generation Z, who have their own unique traits in the modern workplace. The goal of this study is to look at how transformational leadership style and the work environment affect the loyalty of Generation Z workers in Indonesia. Workplace wellness will be looked at as an intervening variable. This study used a sample of 100 respondents selected through purposive sampling technique. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS software. The results of the study showed that the results of the study showed that transformational leadership style and work environment through workplace wellbeing have a significant effect on the loyalty of Generation Z employees in Indonesia.